Ekofeminisme Spritual Starhawk: Hubungan Spiritual Alam pada Novel Mantan Ledek Tayub Karya Dandang A Dahlan - Noer Lailatul Badriya; Agus Purnomo Ahmad Putikadyanto (GHANCARAN: Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2024)
This research is motivated by the existence of elements of spiritual ecofeminism in the Starhawk perspective in the novel Former Ledek Tayub by Dandang A. Dahlan. The purpose of this study is to describe the form of abuse of nature carried out to oppress Ganis characters, classify the categories of spiritual ecofeminism violations experienced by Ganis characters using the Starhawk perspective, and the relationship between Ganis characters and nature. This research is a qualitative descriptive research. With data collection techniques using reading and recording techniques. The results of the research include the form of misuse of nature carried out to oppress the character of Ganis, namely witchcraft, classifying the category of violations of spiritual ecofeminism experienced by the character Ganis in the perspective of Starhawk, namely the violation of interconnection, and the relationship of the character of Ganis with nature, namely the union of Ganis with nature with meditation in tritisan that is carried out and carrying out traditions of gratitude to the Creator of nature such as ruwatan. It can be concluded that spiritual ecofeminism from the perspective of Starhawk, spiritual ecofeminism exists as a form of self-control in utilizing the surrounding nature so that this will prevent the nature of mastery and a form of awareness that humans need to be one with nature to be close to God and create peace of heart and mind.